Girassóis de pedra: imagens e metáforas de uma cidade em busca do tempo - Silva, Valéria Cristina Pereira da [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
A partir do estudo da cidade de Palmas, capital do Estado de Tocatins, o desafio fundamental da tese proposta é analisar o imaginário da cidade projetada e implantada, constituída num tempo compactado e, ainda, como esse espaço organizado no tempo ausente apresenta traços e encaixes na realidade do pós-modernismo. Brasília e Palmas são cidades do tempo ausente que, diferente das demais cidades não planejadas ou projetadas, tem o seu espaço-tempo surgido simultaneamente. Compreendemos teoricamente essa compactação ou simultaneidade, como ausência de tempo. A cidade de Palmas foi projetada e surgiu nessa condição de compactação temporal, sua paisagem urbana detem imagens cheias de simbolismos que jogam com a subjetividade do tempo...

From a study on the city of Palmas, the capital of the state of Tocantins-Brazil, the fundamental problem on the thesis proposal is to analyze the Idea of an implanted pre designed city, settled in a compact period of time and still as IF this organized period of absent time presents treats and fits into post modernism reality. Brasília and Palmas are cities that belong to the so called “absent time” that different from other cities Just haven’t been put into blueprint or pre-planned. They both have time and space emerged simultaneously. We theoretically understand that this compaction or simultaneity as “absence of time”. The city of Palmas has been put into blueprint and came to being into a time compaction condition. It´s urban design and landscaping is filled up with symbolism that simply plays with time subjectivity. The monuments are random temporal maps that represent different periods of time though they are all rather recently made creating an illusion to others perception with the goal of bringing some historic sense to the city. The path to understanding the city and its present/absent temporality on which it has been designed is based on a multiplicity logic that sketches and overlays urban image polysemy... (Complete abstract click electronic acces below)
Keywords: Geografia; Palmas (TO); Post modernism